a+1=12+b-12=c-1=a+b+c-12
Răspunsuri la întrebare
Răspuns de
3
a+1 = 12+b-12 = c-1 = a+b+c-12
a+1 = b = c-1 = a+b+c-12 ⇒ a=b-1 și c=b+1
înlocuim
b=b-1+b+b+1-12
b-1+b+b+1-b=12
2b=12
b=12:2=6 ⇒ a=6-1=5 și c=6+1=7
a+1 = b = c-1 = a+b+c-12 ⇒ a=b-1 și c=b+1
înlocuim
b=b-1+b+b+1-12
b-1+b+b+1-b=12
2b=12
b=12:2=6 ⇒ a=6-1=5 și c=6+1=7
alivas4:
12-12+b=b
Alte întrebări interesante
Limba română,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Chimie,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă
Istorie,
9 ani în urmă